2016
DOI: 10.18632/oncotarget.7209
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale profiling of signalling pathways reveals an asthma specific signature in bronchial smooth muscle cells

Abstract: BackgroundBronchial smooth muscle (BSM) cells from asthmatic patients maintain in vitro a distinct hyper-reactive (“primed”) phenotype, characterized by increased release of pro-inflammatory factors and mediators, as well as hyperplasia and/or hypertrophy. This “primed” phenotype helps to understand pathogenesis of asthma, as changes in BSM function are essential for manifestation of allergic and inflammatory responses and airway wall remodelling.ObjectiveTo identify signalling pathways in cultured primary BSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…58 Interestingly, large-scale transcriptional profiling analyses of ASM cells from asthmatic versus nonasthmatic subjects revealed a marked activation of pathways linked to cell proliferation and growth, vascularization, inflammatory response genes and muscle-tissue-specific responses, such as contractility in asthmatics. 59 Finally, ASM contraction can alter the mechanical properties of the airway wall, promoting mechanotransduction pathways that contribute to remodelling and initiating cascades that synergize with other inflammatory mechanisms. 60 Enhanced vascularity correlates with asthma severity 61 and is a key feature in the airways of people who died from asthma.…”
Section: Restoration Of N Ormal Airway Structure (Mod Elling)mentioning
confidence: 99%
“…58 Interestingly, large-scale transcriptional profiling analyses of ASM cells from asthmatic versus nonasthmatic subjects revealed a marked activation of pathways linked to cell proliferation and growth, vascularization, inflammatory response genes and muscle-tissue-specific responses, such as contractility in asthmatics. 59 Finally, ASM contraction can alter the mechanical properties of the airway wall, promoting mechanotransduction pathways that contribute to remodelling and initiating cascades that synergize with other inflammatory mechanisms. 60 Enhanced vascularity correlates with asthma severity 61 and is a key feature in the airways of people who died from asthma.…”
Section: Restoration Of N Ormal Airway Structure (Mod Elling)mentioning
confidence: 99%
“…3 OncoFinder has previously been applied to many human and non-human systems including cell culture, leukemia and solid cancers, fibrosis, asthma, Hutchinson Gilford and Age-Related Macular Degeneration Disease. [24][25][26][27] The PAS for a given pathway (p) is calculated as follows, 18 , PAS p D P n ARR np Álog CNR n ð Þ, where the functional role of the n th gene product in the pathway is indicated by the activator/repressor role (ARR), which equals 1 for an activator, -1 for a repressor, and intermediate values -0,5; 0,5 and 0 for gene products having intermediate repressor, activator, or unknown roles, respectively. The CNR n value (case-tonormal ratio) is the ratio of the expression level of gene n in the sample under investigation to the average expression level in the control samples.…”
Section: Cross-platform Processing Of Transcriptomic and Proteomic Datamentioning
confidence: 99%
“…But this may change soon. Recently, we performed large-scale profiling analyses of signalling pathway activation signatures in ASM cells of asthmatic and non-asthmatic subjects [ 126 ]. Of the 270 studied signaling pathways, we observed that a substantial fraction of them was significantly more active in asthmatic ASM cells, so that ASM cells of asthmatic patients can be clearly distinguished from those of non-asthmatics.…”
Section: Future Perspectivementioning
confidence: 99%
“…Importantly, the identified pathways predominantly represented pathways linked to cell proliferation and growth, vascularization, inflammatory response and muscle-tissue specific responses, such as contractility. This study was the first to provide clear-cut evidence for an overall, intrinsic “primed” status of asthmatic ASM cells and may reflect the genetically predisposition of the disease [ 126 ].…”
Section: Future Perspectivementioning
confidence: 99%